ANALISIS MODEL PEMBELAJARAN ”KONSEP PASAR TRADISIONAL” DALAM KETERAMPILAN BERKOMUNIKASI PESERTA DIDIK - Al-Ghani, Muhammad Guntur (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
This study aims to analyze the communication skills of students by using the "Traditional Market Concept" learning model which then results are interpreted and processed based on the perspective and conception of the researcher. This research is descriptive quantitative research, in which the results of the assessment of communication skills will be processed into a descriptive form from the researcher's point of view. This research was conducted at the Equality School Package C PKBM Serumpun Tanah Laut with 19 research subjects. This research was conducted in 2 stages, namely before using the "traditional market concept" learning model and after using the "traditional market concept" learning model. The results of the research conducted indicate that this "Traditional Market Concept" learning model can develop the communication skills of students in the Equality Package C School of PKBM Serumpun Tanah Laut. However, this research is a small study and has not included the validation, practicality and effectiveness of the “traditional market concept” learning model. So it is recommended that further research be carried out in the future that can determine the validity, practicality and effectiveness of the "traditional market concept" learning model.